2020
DOI: 10.1212/wnl.0000000000010912
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 70 patients with hydrocephalus due to cobalamin C deficiency

Abstract: Objective:To analyze the clinical characteristics of patients with hydrocephalus secondary to cblC deficiency, and to discuss the optimal strategies for assessing and treating such patients, the clinical and laboratory studies were performed in 70 patients.Methods:A total of 1211 patients were clinically diagnosed with methylmalonic acidemia (MMA) from 1998 to 2019. Among them, cblC deficiency was confirmed in 70 patients with hydrocephalus by brain imaging, biochemical and genetic analysis.Results:Of the 70 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…In summary, ( Nogueira et al, 2008 ; Wang et al, 2010 ; Fischer et al, 2014 ; Liu et al, 2018 ; Wang et al, 2019 ; He et al, 2020a ; He et al, 2020b ; Kang et al, 2020 ; Wang et al, 2021 ), anemia is the most common blood system damage of MMA( Table 1 ), the incidence of which is 21.4–83.3%. Other hematological complications include granulocytopenia, thrombocytopenia, pancytopenia and hemolytic uremia.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, ( Nogueira et al, 2008 ; Wang et al, 2010 ; Fischer et al, 2014 ; Liu et al, 2018 ; Wang et al, 2019 ; He et al, 2020a ; He et al, 2020b ; Kang et al, 2020 ; Wang et al, 2021 ), anemia is the most common blood system damage of MMA( Table 1 ), the incidence of which is 21.4–83.3%. Other hematological complications include granulocytopenia, thrombocytopenia, pancytopenia and hemolytic uremia.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrocephalus is a well‐known life‐threatening complication of combined methylmalonic acidemia and homocystinuria cobalamin C type (Andersson et al, 1999 ; Zhang et al, 2019 ). Although it has been known as a rare complication of methylmalonic acidemia, a recent study reported that the complication is more common in Chinese patients with combined methylmalonic acidemia and homocystinuria cobalamin C type (He et al, 2020 ). Although the genetic diagnosis was not performed for the second baby, it is highly likely that the second baby was also affected by combined methylmalonic acidemia and homocystinuria cobalamin C type.…”
Section: Discussionmentioning
confidence: 99%
“…48 of them had combined MMA and homocysteinemia and 17 had isolated MMA. 222 probands got definite genetic diagnosis [ 4 , 15 ]. Mutation analysis followed the recommendations of the Human Genome Variation Society ( http://www.hgvs.org/mutnomen ).…”
Section: Methodsmentioning
confidence: 99%
“…MMA comprise a group of genetically heterogeneous autosomal recessive disorders caused by defective metabolic pathways involving methylmalonyl-CoA mutase (MUT) or its cofactor, cobalamin [ 1 , 2 ]. MMA encompass 15 diseases caused by the deficient MUT activity or other defects in adenosylcobalamin biosynthesis [ 3 , 4 ]. The clinical manifestations of the patients are complex, ranging from asymptomatic to death.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation